Pengaruh Faktor Makroekonomi Terhadap Indeks Saham Syariah Indonesia - Arthalya, Delta; Pardistya, Irvan Yoga (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of inflation and the Bank Indonesia (BI) rate partially and simultaneously on the Indonesian Sharia Stock Index (ISSI). An increase or decrease in ISSI growth is influenced by macroeconomic factors such as inflation and the BI Rate. The analytical method of this research uses the descriptive analysis method, classic assumption test, multiple regression analysis, and hypothesis testing using SPSS version 25 software. Based on the results of the simultaneous test (F-test), the inflation variable () and the BI Rate () have a significant positive effect on the Indonesian Sharia Stock Index (ISSI). Partial test results (t-test) the inflation variable has no significant effect on ISSI, and the BI Rate variable also has no significant effect on ISSI. The closeness of the relationship between the independent variable (X) and the dependent variable (Y) can be said to be sufficient. In addition, the contribution of inflation () and BI Rate () to ISSI (Y) has a value of 15.8%, as well as the remaining 84.2% is influenced by other variables not included in this study.